Utopia and Religion in Europe in the Seventeenth and Eighteenth Centuries - John Christian Laursen (Histories, 2024)
When European writers of the seventeenth and eighteenth centuries wrote about utopia or their vision of the best possible way to live, they usually included reflections on religion. Religion as it was known in their day was not perfect and had been criticized for causing numerous abuses. If a perfect or near-perfect society were to be imagined, it would have to include a perfect or near-perfect understanding of religion. This could range from atheism to a minimal religion which avoided all the institutional factors, to one in which detailed regulations governed all facets of religion and life. This article reviews and interprets the treatment of religion in a wide range of seventeenth- and eighteenth-century utopias. It concludes that some utopian writers set high goals for change, some settled for lesser reforms, and some left religion as it was while changing other parts of life.